Fraud Triangle Analysis in Preventing Fraud Risks - Nusantara, Panji; Kuntadi, Cris (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This study aims to determine the effect of pressure on fraud, the effect of opportunity on fraud, and the effect of justification on fraud risk based on the previous studies. The research is a literature review. This method was chosen because it is in accordance with the research objectives, namely to determine whether or not the influence of pressure, opportunity and justification for fraud exists. The results of the study indicated that the pressure has a significant positive impact on fraud. The opportunity has a significant positive impact on fraud, the rationalize has a significant positive impact on fraud.